Oral Squamomelanocytic Tumour in a Dog: a Unique Biphasic Cancer. Issue 2 (February 2016) - Muscatello, L.V.; Avallone, G.; Benazzi, C.; Sarli, G.; Porcellato, I.; Brachelente, C.; Brunetti, B.
Summary: In human medicine, squamomelanocytic tumour is a malignant cutaneous neoplasm composed of closely intermingled neoplastic squamous cells and melanocytes. A multinodular gingival tumour in a 16-year-old, mixed breed neutered female dog was examined microscopically. Two populations of neoplastic cells, melanocytic and squamous epithelial cells were intermingled. The melanocytic cells were melan-A positive and cytokeratin AE1–AE3 negative and the squamous component was cytokeratin AE1–AE3 positive and melan-A negative. Bovine papillomavirus was not identified by immunohistochemistry or polymerase chain reaction. A diagnosis of squamomelanocytic tumour was made.